2017
DOI: 10.1111/1745-9125.12129
|View full text |Cite
|
Sign up to set email alerts
|

Heuristics and Biases, Rational Choice, and Sanction Perceptions*

Abstract: The relevance of several cognitive heuristics and related biases for rational choice perspectives on crime, and for perceptions of sanction risk, were investigated. We present findings from a series of randomized experiments, embedded in two nationwide surveys of American adults (18 and older) in 2015 (N = 1,004 and 623). The results reveal that offender estimates of detection risk are less probabilistically precise and more situationally variable than under prevailing criminological perspectives, most notably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 113 publications
(185 reference statements)
2
96
0
Order By: Relevance
“…Systematic departures from this standard model have been subsequently studied by Thomas, Loughran, and Piquero () and by Pogarsky et al. (). Such a set of strategies will then allow for us to move away from merely testing whether potential offenders are “rational” and instead move into more policy‐related concerns.…”
Section: State Of Criminological Rational Choice Theorymentioning
confidence: 94%
“…Systematic departures from this standard model have been subsequently studied by Thomas, Loughran, and Piquero () and by Pogarsky et al. (). Such a set of strategies will then allow for us to move away from merely testing whether potential offenders are “rational” and instead move into more policy‐related concerns.…”
Section: State Of Criminological Rational Choice Theorymentioning
confidence: 94%
“…Scholars have investigated time preferences (Loughran, Paternoster, & Weiss, ; Nagin & Pogarsky, , ), sanction risk perceptions (Loughran, Pogarsky, Piquero, & Paternoster, ; Thomas, Hamilton, & Loughran, ), sanction risk perception updating (Anwar & Loughran, ; Thomas, Loughran, & Piquero, ; Wilson, Paternoster, & Loughran, ), ambiguity (Casey & Scholz, , ) and ambiguity aversion (Loughran, Paternoster, Piquero, & Pogarsky, ; Pickett, Loughran, & Bushway, ), reference dependence (Bushway & Owens, ; Pickett, Barnes, Wilson, & Roche, ), social preferences (Jaynes & Loughran, ), and heuristics (Pickett, ; Pogarsky, Roche, & Pickett, ). This list is not exhaustive, nor are the potential applications of behavioral economics to criminological theory yet complete.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Since its original formulation, rational choice theory has been the subject of academic scrutiny with further refinements being made. Most recently, [32,33], the discussion has distinguished between application within two schools: the neoclassical utility focus in which criminal decision makers are seen as objective cost-benefit calculators [34] able to derive the outcome that maximises their own personal utility; and studies that accept the fallibility inherent in human decision making and that recognises imperfect or bounded rationality [35]. In the latter case, an individual's ability to weigh accurately these different sides of the scales of risk and reward is of necessity bounded by limited availability of information and the accuracy with which they can evaluate 'future' costs in terms of their equivalent current impact.…”
Section: The Criminal Profit Formula and Effectiveness Of Approachmentioning
confidence: 99%
“…Court proceedings point to a distinction between the money laundering offence and the predicate crime in how they are prosecuted and sentenced. For one participant within law enforcement, the disparity in sentencing for 'related' crimes such as drug trafficking and money laundering simply did not make sense 32 and that there was 'no message that money laundering and predicate crimes are equal'. Another participant suggested that the judiciary needed education regarding the sentencing guidelines with further guidance through both the court of appeal and the sentencing council.…”
Section: Asset Recovery and Sentencing Deterrentmentioning
confidence: 99%